A Copa de 2014 na capital mineira e relações com as políticas públicas de esporte e lazer: estudo a partir de projetos que compõem o planejamento estratégico integrado do Estado de Minas Gerais e da Prefeitura de Belo Horizonte - Carlos Eduardo Dias Munaier Lages (2012)
The present study aims to understand the concepts of Public Policies to Sport and Leisure, and the popular participation in three projects of integrated Strategic Planning of the World Cup in 2014 in the State of Minas Gerais and the city of Belo Horizonte and the discourse of their makers, as well as analyze the actions included in those projects that focus on the experiences of sport and leisure of Belo Horizonte. The research was organized into four stages: an exposition of theoretical concepts and impacts related to mega events and some approaches to leisure, a theoretical exposition of the concepts of popular participation and public policy, emphasizing those of sport and leisure, an analysis of the projects chosen for research (Modernization of the Mineirão Stadium, Stadiums Alternative, Urban Mobility) and the Integrated Strategic Planning and finally, an analysis of the interviews which were conducted with six managers directly related to the formulation and / or implementation of projects. To carry out the research, were created four categories of analysis: actions listed on the projects that can influence the experiences of sport and leisure of belohorizontino people, Conceptions of public policies for sport and leisure, Conceptions of popular participation and impacts and legacies. To accomplish the goals established in this investigation was adopted a method of documentary research and field of qualitative character. The analysis of documents was made based on the technique of content analysis by Bardin (1979). Yet for field research, was used a semi-structured interview seeking to give freedom for the interviewee to explore and argue about relevant issues on his mind, as proposed by Triviños Neto (2004). The final remarks were made inferences relating to the theoretical concepts discussed in the first two chapters with the analyzes from the strategic planning and projects chosen for analysis as well as the reports made by the managers interviewed. Thus, it was found that several interventions proposed by the managers and projects that influence the experiences of sport and leisure of belohorizontino people the proposals were based on a market-oriented logic. It was found that some managers have tangential and superficial conceptions about public policies to sport and leisure, with no clear its importance and its relationship with the organization of World Cup 2014, and very large surface and with respect to participation popular, making it unclear whether this actually occurred in the process of organizing the mega event. Regards to the impact and legacy, most managers perceive the achievement of the World Cup in the capital as a "business" meaning, an opportunity to advance decisions and government resources, the increased flow of tourists and the promotion of the image of the city.